Three new species of endogean Osoriini from southern Spain (Coleoptera: Staphylinidae: Osoriinae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2007)
Three endogean species of the osoriine genus Lusitanopsis Coiffait, 1961 from southern Spain are described and illustrated: L. andujari sp. n. (Valencia: Sierra d’Aitana), L. segurica sp. n. (Castilla-La Mancha: Sierra de Segura), and L. meybohmi sp. n. (Andalucía: Sierra de Aracena). The distributions of these species are mapped. Additional records of Geomitopsis franzi Coiffait, 1978 from the Canary Islands are reported, including a first record from La Palma. Keywords Coleoptera, Staphylinidae, Osoriinae, Palaearctic region, Spain, taxonomy, new species, new records, endogean fauna. Nomenclatural Acts andujari Assing, 2007 (Lusitanopsis), spec. n. meybohmi Assing, 2007 (Lusitanopsis), spec. n. segurica Assing, 2007 (Lusitanopsis), spec. n.